Border carbon adjustments: Should production or consumption be taxed? - Martin, Will (European University Institute, 2022)
Border Carbon Adjustment (BCAs) may play an important role in lowering the economic costs of greenhouse gas mitigation and in overcoming political-economy constraints on use of carbon taxes or equivalent measures. A carbon tax plus a full BCA (CTBA) could deal with the competitiveness challenges arising from carbon taxes by using the WTO’s National Treatment principle to apply equal levies on domestic production and on imports, and by symmetrically rebating the carbon tax on exports in the manner of a VAT export rebate. This approach would shift the base for carbon taxation from output to consumption and intermediate input use and potentially lower the cost of achieving reductions in emissions. It would avoid the massive measurement and compliance problems associated with BCAs based on foreign emission intensities. By contrast, proposals for import-only BCAs would distort prices of importables relative to exportables, create competitiveness concerns in export industries, generate economic waste and likely create highly divisive trade conflicts and deterioration in the terms of trade for developing countries.